Pengaruh Kemampuan Numerik dan Intensitas Latihan Soal Terhadap Hasil Belajar Aplikasi Pengolah Angka (Spreadsheet) - Fitri Juita; Yulhendri Yulhendri (Jurnal Ecogen, 2019)
This research aims to: (1) the effect of numerical ability and intensity of exercise to learn the results of processing a number of applications (spreadsheet). (2) the effect of the learning outcomes of numerical ability processing a number of applications (spreadsheet). (3) the effect of exercise intensity about the learning outcomes of processing a number of applications (spreadsheet). This type of research is descriptive quantitative research for this study presents the results of processing the data obtained from the study sample by using SPSS version 21. The instrument used in this study a questionnaire used to measure a variable intensity exercise. The population in this study were all students of class X Accounting totaling 102 people. The sample in this study amounted to 81 people were selected using random sampling techniques. The results of this study stated that: (1) the ability of numerical and intensity exercise influence on learning outcomes spreadsheet (2) of numerical ability has no effect on learning outcomes spreadsheet (3) the intensity of exercises influence on learning outcomes spreadsheet. Keywords: learning outcomes, numerical ability, intensity exercises.